Effects of chemoradiotherapy on surface PD-L1 expression in esophageal cancer and its implications for immunotherapy - Hampe, Lovis; Küffer, Stefan; Niemeier, Tim; Scheele, Niklas Christian; Hampe, Laetitia Zoe; Riedl, Anna Luisa; Fischer, Laura Anna; Ziegler, David Alexander; Leu, Martin; Dröge, Leif Hendrik; König, Alexander; Ghadimi, Michael; et al. (Frontiers in Immunology, 2024)
BackgroundEsophageal cancer has a poor prognosis despite treatment advancements. Although the benefit of neoadjuvant chemoradiotherapy (CRT) followed by adjuvant immunotherapy is evident, the effects of CRT on PD-L1 expression in esophageal cancer are not well understood. This study examines the impact of neoadjuvant CRT on PD-L1 surface expression in esophageal cancer both in vitro and in vivo considering its implications for immunotherapy.MethodsPD-L1 expression dynamics were assessed in esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC) cell lines (OE-33, FLO-1, KYSE-180) treated with Carboplatin, Paclitaxel, radiotherapy (RT), and CRT. PD-L1 expression was measured by flow cytometry at 48- and 72 hours post-treatment. Temporal changes of surface PD-L1 were further investigated in KYSE-180 cells following RT, up to 168h after treatment. Additionally, PD-L1 expression was analyzed via immunohistochemistry in histological samples from 19 patients (9 EAC, 10 ESCC) treated with neoadjuvant CRT according to the CROSS-scheme.ResultsPD-L1 expression was upregulated the most by Carboplatin, a combination of chemotherapy, or CRT in all cell lines. Higher irradiation doses were more effective in inducing PD-L1 expression, while Paclitaxel alone did not consistently increase PD-L1. The ESCC cell line KYSE-180 showed the highest relative PD-L1 increase. Measurement of PD-L1 kinetics revealed a transient upregulation of surface PD-L1, which peaked at 72 hours post-treatment and subsequently returned to baseline levels by 168 hours. In vivo, data demonstrated no significant PD-L1 expression changes when comparing pre- and post-treatment levels.ConclusionsChemotherapy, RT, and CRT can induce PD-L1 expression in various esophageal cancer cell lines. However, neoadjuvant CRT according to the CROSS protocol does not significantly induce PD-L1 in vivo. Considering the difference in time between pre- and post-therapeutic measurements, these findings suggest that PD-L1 upregulation due to neoadjuvant therapy may be transient in vivo as well. This highlights the potential benefit of administering immunotherapy in a neoadjuvant setting.